(untitled) (American Journal of Islam and Society, 2013)
Much has been written about religion and secularism in Turkey over the past decades, but detailed histories of the late Ottoman and modern Turkish ulema have been few and far between. Therefore, this recent book by Amit Bein is a welcome and a much needed contribution to the literature on the Turkish ulema and to the literature on religion in modern Turkey in general. It charts the vicissitudes of the ulema during a period of dramatic change from the late nineteenth century until roughly 1960. Bein shows the multiple challenges the ulema faced during successive rounds of political and social reform and the various approaches that they took in response. The diversity of opinion and political orientation within the ulema corps are on full display – from the most ardent nationalist figures, who supported state reforms in all respects, to the staunchest enemies of the republican regime. This book conveys a nuanced understanding of who the Turkish ulema were and how they navigated the empire-to-republic transition ...